Does Renewable Energy Matter to Achieve Sustainable Development Goals? The Impact of Renewable Energy Strategies on Sustainable Economic Growth - Chen, Jie; Su, Fan; Jain, Vipin; Salman, Asma; Tabash, Mosab I.; Haddad, Akram M.; Zabalawi, Eman; Abdalla, Alaa Amin; Shabbir, Malik Shahzad (Frontiers in Energy Research, 2022)
The influences of renewable and conventional energy consumption on ecological sustainability are stayed unclear because of the dynamic economic and innovative framework. This investigation gives a new perception by exploring the association between productions of various sources of renewable energies such as, hydropower, wind power, solar pv, geothermal, and biomass, and economic growth encapsulating capital, government spending, and trade openness. This research used a heterogeneous approach for panel data as well as second generational tools for econometrics, which allow for cross-sectional reliance as well as slope heterogeneity. The assessment of long-term impacts led by AMG, alongside CCEMG and MG assessors uncovered that other than different factors like government spending, trade openness, capital accumulation, renewables energy, and conventional energy use significantly adds to the economic prosperity of the selected Asian economies. This study has revealed the substantial reason to back up the feedback assumptions between renewable energy sources, economic growth, using the Dumitrescu and Hurlin analysis. In terms of policy, this empirical analysis suggests enacting impactful policies that encourage green power and economic reform in an attempt to lessen CO2 concentrations in the biosphere.